Jumlah leukosit, persentase limfosit dan persentase monosit ayam petelur jantan setelah perlakuan penambahan serbuk daun kelor pada pakan - Muhammad Anwar Djaelani; Kasiyati Kasiyati; Sunarno Sunarno (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2020)
This study aimed to observe the effect of Moringa leaf powder as a feed addition to the number of leukocytes, the percentage of lymphocytes and the percentage of monocytes monocytes in chicken. This study used a Completely Randomized Design consisting of five treatments, one treatment group and four treatment groups with basic feed and basic feed which were added with some levels of Moringa leaf powder. Treatment group P0: Basic feed, without the addition of Moringa leaf powder as a control. Treatment group P1: Basic feed added with 1% Moringa leaf powder. P2 treatment group: Basic feed given 2% Moringa leaf powder. P3 treatment group: Basic feed given with additional Moringa leaf powder 3%. P4 treatment group: Basic feed given 4% Moringa leaf powder. The results showed that Moringa leaf powder as an additional feed did not significantly influence the number of leucocyte, percentage of lymphocites and percentage of monocytes among treatment group (P> 0.05). The conclusion of this study is that the addition of Moringa leaf powder to the feed of chicken has the potential to maintain the profile of white blood at normal values, which is indicated by the number of leukocytes, the percentage of lymphocytes and the percentage of monocytes.